Fight fire with fire: Neurobiology of capsaicin-induced analgesia for chronic pain - Arora, Vipin (Pharmacol Ther, 2020)
Capsaicin, the pungent ingredient in chili peppers, produces intense burning pain in humans. Capsaicin selectively activates the transient receptor potential vanilloid 1 (TRPV1), which is enriched in nociceptive primary afferents, and underpins the mechanism for capsaicin-induced burning pain. Paradoxically, capsaicin has long been used as an analgesic. The development of topical patches and injectable formulations containing capsaicin has led to application in clinical settings to treat chronic pain conditions, such as neuropathic pain and the potential to treat osteoarthritis. More detailed determination of the neurobiological mechanisms of capsaicin-induced analgesia should provide the logical rationale for capsaicin therapy and help to overcome the treatment’s limitations, which include individual differences in treatment outcome and procedural discomfort. Low concentrations of capsaicin induce short-term defunctionalization of nociceptor terminals. This phenomenon is reversible within hours and, hence, likely does not account for the clinical benefit. By contrast, high concentrations of capsaicin lead to long-term defunctionalization mediated by the ablation of TRPV1-expressing afferent terminals, resulting in long-lasting analgesia persisting for several months. Recent studies have shown that capsaicin-induced Ca(2+)/calpain-mediated ablation of axonal terminals is necessary to produce long-lasting analgesia in a mouse model of neuropathic pain. In combination with calpain, axonal mitochondrial dysfunction and microtubule disorganization may also contribute to the longer-term effects of capsaicin. The analgesic effects subside over time in association with the regeneration of the ablated afferent terminals. Further determination of the neurobiological mechanisms of capsaicin-induced analgesia should lead to more efficacious non-opioidergic analgesic options with fewer adverse side effects.